Management consultancy - a new profession? - Muzio, Daniel (Henry Stewart Talks, 2015)
The success of management consultancy, Professions, professionals and professionalism, Management consultancy as a profession, Consultancy and the failure to professionalize, Comparing large consultancy firms & corporate professionalism